Reactive dicarbonyl compounds cause Calcitonin Gene-Related Peptide release and synergize with inflammatory conditions in mouse skin and peritoneum - Becker, Anna; Auditore, Andrea; Pischetsrieder, Monika; Meßlinger, Karl; Fleming, Thomas; Reeh, Peter; Sauer, Susanne (Journal of Biological Chemistry, 2020)
The plasmas of diabetic or uremic patients and of those receiving peritoneal dialysis treatment have increased levels of the glucose-derived dicarbonyl metabolites like methylglyoxal (MGO), glyoxal (GO), and 3-deoxyglucosone (3-DG). The elevated dicarbonyl levels can contribute to the development of painful neuropathies. Here, we used stimulated immunoreactive Calcitonin Gene–Related Peptide (iCGRP) release as a measure of nociceptor activation, and we found that each dicarbonyl metabolite induces a concentration-, TRPA1-, and Ca2+-dependent iCGRP release. MGO, GO, and 3-DG were about equally potent in the millimolar range. We hypothesized that another dicarbonyl, 3,4-dideoxyglucosone-3-ene (3,4-DGE), which is present in peritoneal dialysis (PD) solutions after heat sterilization, activates nociceptors. We also showed that at body temperatures 3,4-DGE is formed from 3-DG and that concentrations of 3,4-DGE in the micromolar range effectively induced iCGRP release from isolated murine skin. In a novel preparation of the isolated parietal peritoneum PD fluid or 3,4-DGE alone, at concentrations found in PD solutions, stimulated iCGRP release. We also tested whether inflammatory tissue conditions synergize with dicarbonyls to induce iCGRP release from isolated skin. Application of MGO together with bradykinin or prostaglandin E2 resulted in an overadditive effect on iCGRP release, whereas MGO applied at a pH of 5.2 resulted in reduced release, probably due to an MGO-mediated inhibition of transient receptor potential (TRP) V1 receptors. These results indicate that several reactive dicarbonyls activate nociceptors and potentiate inflammatory mediators. Our findings underline the roles of dicarbonyls and TRPA1 receptors in causing pain during diabetes or renal disease.
CRIS-Team Scopus Importer:2020-05-26

Spontaneous activity of specific C-nociceptor subtypes from diabetic patients and mice: Involvement of reactive dicarbonyl compounds and (sensitized) transient receptor potential channel A1 - Becker, Anna; Babes, Alexandru; Düll, Miriam; Khalil, Mohammad; Kender, Zoltan; Gröner, Jan; Namer, Barbara; Reeh, Peter; Sauer, Susanne (Journal of the Peripheral Nervous System, 2023)
Background: Diabetic metabolism causes changes of the chemical milieu including accumulation of reactive carbonyl species, for example, methylglyoxal (MGO). MGO activates chemosensitive TRPA1 on nociceptors, but the contribution to neuronal pathophysiology causing pain and hyperalgesia in diabetic neuropathy is not fully understood. Methods: We employed single-nerve-fiber recordings in type 2 diabetes patients with (spDN) and without cutaneous pain (DN) and in streptozotocin-diabetic and healthy mice. In mice, we measured Ca++ transients in cultured DRG neurons and stimulated CGRP release from hairy skin. Results: In diabetic patients, we recorded a large proportion of pathologically altered nerve C-fibers (79%). In spDN patients we found a higher percentage (72%) of spontaneously active C-nociceptors than in DN patients (15%). The proportion of spontaneous activity was highest among pathological fibers with mechanoinsensitive fiber properties which are particularly sensitive to MGO in contrast to mechanosensitive fibers. Mouse polymodal nociceptors, in contrast to purely mechanosensitive C-fibers, showed highest prevalence of TRPA1-related chemosensitivity. In diabetic mice about 37% of polymodal nociceptors developed spontaneous activity and exhibited significantly greater MGO responses, indicating sensitized TRPA1 receptors. Low-threshold mechanosensitive Aδ-fibers were vigorously activated by MGO but independently of TRPA1 activation. Interpretation: Our translational findings suggest that TRPA1-expressing C-nociceptors, which in human correspond to mechanoinsensitive and in mice to polymodal nociceptors, are especially vulnerable to develop spontaneous activity. Those two different nociceptor classes might share the functional role as dicarbonyl-sensitive chemosensors and represent the critical nociceptor population that support the development of pain and hyperalgesia in diabetic neuropathy.
CRIS-Team Scopus Importer:2023-05-19
Keywords: calcitonin gene-related peptide; cutaneous nociceptor; excitability; mechanoinsensitive C-fiber; methylglyoxal; microneurography; neuropathic pain